2015
DOI: 10.1016/j.egypro.2015.03.184
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Solar Field Inlet and Outlet Temperature on the Cost of Electricity in a Molten Salt Parabolic Trough Power Plant

Abstract: While the positive effect of raising turbine inlet temperature to increase overall plant efficiency is often quoted and discussed, another figure is mentioned to a much lesser extent: The HTF outlet temperature at the steam generator exit, which also has a profound influence on cycle efficiency due to the fact that allowing higher temperatures allows moving to much higher evaporator pressures and, thus, higher cycle efficiencies. This paper aims at evaluating potential benefits of increasing the lower HTF temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Richert et al . studied the influence of solar field inlet and outlet temperature on the cost of electricity in a molten salt parabolic trough power plant. Jafari et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Richert et al . studied the influence of solar field inlet and outlet temperature on the cost of electricity in a molten salt parabolic trough power plant. Jafari et al .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [33] performance assessment of solar assisted absorption heat pump system with parabolic trough collectors. Richert et al [34] studied the influence of solar field inlet and outlet temperature on the cost of electricity in a molten salt parabolic trough power plant. Jafari et al [35] performed a new desalination system using a combination of heat pipe, evacuated tube and parabolic through collector.…”
Section: Introductionmentioning
confidence: 99%
“…al. (2019) reported that researches on channel/collector depth(Delfani et al, 2019) and length(Do Ango et al, 2013), number of collectors(Zadeh et al, 2015), solar tracking system(Rizk & Chaiko, 2008), absorber plate design parameters (tube diameter(Kim & Seo, 2007), tube spacing(Ghamari & Worth, 1992), fin thickness(Pottler et al, 1999)), booster diffuse reflector(Tripanagnostopoulos et al, 2002), collector tilt angle(Handoyo & Ichsani, 2013), PV module type(Jiang et al, 2011), glass thickness(Bakari et al, 2014), glazing material(Dondapati et al, 2018), anti-reflective coating(Ali et al, 2014), riser-header configuration(Zwalnan et al, 2021), riser location(Ekramian et al, 2014), thermal conductivity of tedlar(Koech et al, 2012), thermal insulation(Kehrer et al, 2003), absorber material(Kennedy, 2002), absorber thickness(Belaidi et al, 2008), fins(Ozakin et al, 2020), multi-inlet(Hassan & Abo-Elfadl, 2018), PV cell material(Dhass et al, 2020), solar radiation(Hamrouni et al, 2008), relative humidity(Ettah et al, 2012), wind speed(Ozakin & Kaya, 2019), ambient temperature(Alshawaf et al, 2020), accumulated dust(Adinoyi & Said, 2013), mass flow rate(Yakut, 2021), thermal resistance(Zondag, 2008), inlet and outlet temperatures(Richert et al, 2015), heat loss coefficient(Sekhar et al, 2009), heat removal factor(Malvi et al, 2017), packing factor(Ji et al, 2006), and effect of fan(Arslan et al, 2020) were carried out in the l...…”
mentioning
confidence: 99%